2011
DOI: 10.1093/rof/rfr006
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Preference and the New Year Effect of Assets with Lottery Features*

Abstract: This paper examines whether investors exhibit a New Year's gambling preference and whether such preference impacts prices and returns of assets with lottery features. In January, calls options have higher demand than put options, especially by small investors. In addition, relative to atthe-money calls, out-of-the-money calls are the most expensive and actively traded. In the equity markets, lottery-type stocks in the US outperform their counterparts mainly in January, but tend to underperform in other months.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 81 publications
4
68
1
1
Order By: Relevance
“…We identify lottery-like stocks by constructing an index that ranks securities by how much they share features of attractive monetary gambles (i.e., low price, high volatility, and high skewness). This lottery index (LIDX) is inspired by Kumar (2009b) and has been used in other studies to identify lottery-type stocks (e.g., Doran et al (2011), Kumar et al (2011)). We then measure return comovement among lottery-like stocks by regressing stock returns on a portfolio of high-LIDX stocks while controlling for commonly used return factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identify lottery-like stocks by constructing an index that ranks securities by how much they share features of attractive monetary gambles (i.e., low price, high volatility, and high skewness). This lottery index (LIDX) is inspired by Kumar (2009b) and has been used in other studies to identify lottery-type stocks (e.g., Doran et al (2011), Kumar et al (2011)). We then measure return comovement among lottery-like stocks by regressing stock returns on a portfolio of high-LIDX stocks while controlling for commonly used return factors.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that investors with a stronger propensity to gamble exhibit a strong preference for lottery-like stocks (Kumar (2009b), Kumar et al (2011)), trade more frequently (Dorn andSengmueller (2009), Hoffmann andShefrin (2011), and Grinblatt and Keloharju (2009)), and substitute between lottery gambling and stock trading (Gao and Lin (2011)). Furthermore, Doran et al (2011) show that gambling preferences of individual investors during the New Year influence the January prices and returns of assets with lottery features, and Coelho et al (2010) show that gambling-motivated retail investors trade stocks of bankrupt firms for a shot at extreme payoffs.…”
mentioning
confidence: 99%
“…Kumar (2009) finds that trades in lottery-like assets have a negative impact on investors' portfolio performance and Page, Spalt, and even observe a herding effect of such trades. As for the derivatives market Doran, Jiang, and Peterson (2011) find that retail investors are more attracted by lottery-like assets, such as out-of-the-money options, around New…”
mentioning
confidence: 99%
“…These include stocks that have prices greater than five dollars, low analyst coverage, poor credit ratings, high short-sale constraints, high leverage, or for non-January months (see, e.g., George and Hwang (2011), Avramov et al (2013), Boehme et al (2009), Johnson (2004, and Doran, Jiang, and Peterson (2012)). …”
Section: Subsample Analysismentioning
confidence: 99%
“…2 The long list of candidate explanations includes those based on expected idiosyncratic skewness (Boyer, Mitton, and Vorkink (2010)), coskewness (Chabi-Yo and Yang (2009)), maximum daily return (Bali, Cakici, and Whitelaw (2011)), retail trading proportion (Han and Kumar (2013)), one-month return reversal (Fu (2009) and Huang, Liu, Rhee, and Zhang (2009)), illiquidity (Bali and Cakici (2008) and Han and Lesmond (2011)), uncertainty (Johnson (2004)), average variance beta (Chen and Petkova (2012)), and earnings surprises (Jiang, Xu, and Yao (2009) and Wong (2011)). In addition, several papers show that the idiosyncratic volatility puzzle is stronger among stocks that are short-constrained (Boehme, Danielsen, Kumar, and Sorescu (2009) and George and Hwang (2011)), in financial distress (Avramov, Chordia, Jostova, and Philipov (2013)), have low investor attention (George and Hwang (2011)), have prices greater than five dollars (George and Hwang (2011)), and in non-January months (George and Hwang (2011) and Doran, Jiang, and Peterson (2012)). …”
Section: Introductionmentioning
confidence: 99%